2003
DOI: 10.1021/es020924h
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Response of Lakes in the Adirondack Region of New York to Declines in Acidic Deposition

Abstract: Long-term changes in the chemistry of wet deposition and lake water were investigated in the Adirondack Region of New York. Marked decreases in concentrations of SO 4 2-and H + in wet deposition have occurred at two sites since the late 1970s. These decreases are consistent with long-term declines in emissions of sulfur dioxide (SO 2 ) in the eastern United States. Changes in wet NO 3 -deposition and nitrogen oxides (NO x ) emissions have been minor over the same interval. Virtually all Adirondack Lakes have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
253
2
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 297 publications
(268 citation statements)
references
References 34 publications
12
253
2
1
Order By: Relevance
“…Signs of oscillations with 20, 11, 8-9, 3-5 and 2 years long periods can be observed, that generally corresponds to the results of earlier studies (Glazacheva, 1988;Klavins et al, 2002a). Increase of water color, known also as brownification, was frequently reported in many lakes and rivers of the Northern hemisphere (Driscoll et al, 2003;Frey and Smith, 2005;Monteith et al, 2007;Erlandsson et al, 2008;Haaland et al, 2010), including Latvian rivers as well (Klavins et al, 2012). Our data show that despite low data quality and short period of observations , statistically significant upward trends of color values can be found in both rivers (Table 3).…”
Section: Resultssupporting
confidence: 90%
“…Signs of oscillations with 20, 11, 8-9, 3-5 and 2 years long periods can be observed, that generally corresponds to the results of earlier studies (Glazacheva, 1988;Klavins et al, 2002a). Increase of water color, known also as brownification, was frequently reported in many lakes and rivers of the Northern hemisphere (Driscoll et al, 2003;Frey and Smith, 2005;Monteith et al, 2007;Erlandsson et al, 2008;Haaland et al, 2010), including Latvian rivers as well (Klavins et al, 2012). Our data show that despite low data quality and short period of observations , statistically significant upward trends of color values can be found in both rivers (Table 3).…”
Section: Resultssupporting
confidence: 90%
“…It also suggests a bias towards favoring systems with high DOC concentrations, which usually means northern humic-type ones. Since some authors [14,37,48,62,69] observed that trends are correlated with initial concentration levels, it is clear that, in practice, not considering low concentrations introduces a bias towards the measurement of higher trends. On the other end of the spectrum, de Wit et al [52] wrote: "samples with exceptionally high TOC concentrations (>18 mg C L −1 ) were excluded from the dataset" because "TOC in these samples had been modified by in-stream processes rather than being products of soil processes", reasoning difficult to understand when studying OC behavior in natural systems.…”
Section: Data Censoringmentioning
confidence: 99%
“…Increases in surface water DOC has been well documented in a number of regions in Europe and North America (Evans et al 2005;Skjelkvåle et al 2001;Kopáček et al 2006;Driscoll et al 2003;Jeffries et al 2003). Although the drivers associated with this increase are speculative, suggestions include decreased acidic deposition, increased temperatures owing to global warming, changes in hydrology and changes in land use (Evans et al 2005).…”
Section: Factors Confounding Recovery Of Surface Watersmentioning
confidence: 99%